2019
DOI: 10.1186/s13019-019-0894-y
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral single-port thoracoscopic surgery for bilateral pneumothorax or pulmonary bullae

Abstract: Background Rapid rehabilitation surgery has become a widely accepted approach. Thoracic surgeons have attempted in many ways to make surgery less invasive. We combined tubeless technology, single-port technology and mediastinum approach for the treatment of simultaneous bilateral primary spontaneous pneumothorax(PSP)or pulmonary bullae. And we evaluated its therapeutic effect. This study aimed to investigate if tubeless single-port video-assisted thoracic surgery (Tubeless-SPVATS) via anterior med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…International consensus recommends surgical intervention after the first ipsilateral or contralateral recurrence, as mentioned in the leading guidelines. 2,14,15 Although some literature advocates early surgery for patients presenting with blebs or bullae after a first episode of PSP, 4,[16][17][18] as well as some physicians proving the feasibility and safety of performing single-stage unilateral or bilateral video-assisted thoracic surgery (VATS) in selected patients with PSP with contralateral blebs/bullae using different techniques, [19][20][21][22][23][24] the effect of contralateral bleb excision in the prevention of contralateral recurrence with the same anesthesia for ipsilateral PSP remains controversial. No study or follow-up data show the outcome or effect of the contralateral surgery.…”
Section: Perspectivementioning
confidence: 99%
“…International consensus recommends surgical intervention after the first ipsilateral or contralateral recurrence, as mentioned in the leading guidelines. 2,14,15 Although some literature advocates early surgery for patients presenting with blebs or bullae after a first episode of PSP, 4,[16][17][18] as well as some physicians proving the feasibility and safety of performing single-stage unilateral or bilateral video-assisted thoracic surgery (VATS) in selected patients with PSP with contralateral blebs/bullae using different techniques, [19][20][21][22][23][24] the effect of contralateral bleb excision in the prevention of contralateral recurrence with the same anesthesia for ipsilateral PSP remains controversial. No study or follow-up data show the outcome or effect of the contralateral surgery.…”
Section: Perspectivementioning
confidence: 99%
“…Lunxu Liu, from the Department of Thoracic Surgery of West China Hospital of Sichuan University, demonstrates the value of single-port thoracoscopic surgery in treating multiple primary lung cancers in 2014. Further exploration of this method after this, the majority of the lesions involved bilateral lungs disease like bilateral isolated metastases [ 14 ], bilateral pulmonary bullae with unilateral/bilateral pneumothorax and lung volume reduction surgery for patients with severe emphysema [ 15 ]. And may involve empyema [ 16 ], bilateral pleural biopsies, bilateral thoracic sympathectomy [ 17 , 18 ] and thymoma complicated with myasthenia gravis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for selection was based on surgical operator’ own clinical experience. After we managed the journals searches [ 2 7 , 9 , 14 , 15 , 17 24 ] and summaries of related work experience in our department, there are several caveats to our study that are noted throughout and summarized below. Such patients without a complicating pleural infection, thoracic trauma with hemopneumothorax and rib fractures, a history of prior pleurodesis or any subtle pleural nodularity or thickening is found on preoperative chest CT scans; With appropriate monitoring of cardiopulmonary parameters it can be performed safely and is well tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous anesthesia with spontaneous breathing has been applied in VATS, as it is deemed to offer fewer side effects than anesthesia with endotracheal intubation, thus potentially enabling faster postoperative recovery. Many studies have demonstrated that SV-VATS bullectomy is safe and feasible for the treatment of PSP (9,13,31). PSP patients are often young and have good pulmonary function, stable hemodynamics, and only few comorbidities if at all, making the effects of intravenous anesthesia more predictable and stable intraoperative physiologic management is more easily maintained.…”
Section: Discussionmentioning
confidence: 99%